Propagation of Gaharu Plant Gyrinops Versteegii Species Provenant Beringin Throught in Vitro Culture - Aida Muspiah; Tri Mulyaningsih; Eka Sunarwidhi Prasedya (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Grynops verstegii is a non-timber forest product commodity that has a very high economic value. People know this tree as the agarwood tree. In Lombok, the Beringin provenance is one of the leading provenances, so it is very important to conserve its germplasm. This study aims to find alternatives for gaharu development through seed production using in vitro culture techniques. This research was carried out in July 2021 at the Tissue Culture Unit of the Immunobiology Laboratory, University of Mataram. In this experiment there were 8 media treatments with different concentrations of BAP (Ssitokini) and NAA (auxin). The results showed that callus growth occurred on MS 1, MS 3, MS 4, MS 6, and MS 7 media. However, the best growth was obtained in MS 1 treatment with a combination of 1.0 ppm BAP and 0.5 ppm NAA. While most of the samples experienced browning and contamination.